Pengaruh Perbandingan Pati Biji Sorgum (Sorghum Bicolor (l.) Moench) dan Poly Lactic Acid (PLA) terhadap Karakteristik Plastik Biodegradable - Siti Sarifah; Yusmaniar Yusmaniar; Zulmanelis Darwis (Jurnal Riset Sains dan Kimia Terapan, 2017)
This study aims to determine the effect of Sorghum and Poly lactic acid (PLA) on the plastic characteristics that can be seen from tensile strength, water resistance, and biodegradability. The method used blending (mixing) sorghum seed starch, PLA, glycerol, acetic acid, and maleic anhydride. From the results of infrared spectrum analysis on the visible plastic peak area 2250-2300 cm-1 which indicates the absorption of carbon dioxide. This plastic has an optimum water resistance of 92.76% in the ratio of Pati 0.6g: PLA 2.6g. The optimum tensile test results in a comparison of 0.2g starch: PLA 3g with a value of 10.58 Mpa. Optimum biodegradation test results in starch ratio of 0.6g: PLA 2.6g of 13.61%. From the data obtained can be concluded the optimum biodegradation and water endurance test on the ratio of starch 0.6g: PLA 2.6g. Keyword: Seaweed starch, PLA, glycerol, maleic anhydrous, biodegraded plastic